A multi-heat-resistant ultra-thin intumescent fire-retardant coating, preparation method and application thereof
By using modified graphene oxide, hydrophobic aerogel material, expandable graphite and aqueous petroleum resin in expandable fireproof coatings, it forms a four-phase composite carbon source, and uses triple expansion insulation mechanism to solve the shortcomings of existing fireproof coatings in terms of immersion resistance, shielding performance, carbon layer strength and thermal resistance at room temperature, and realizes the multiple thermal resistance function of ultra-thin coatings and excellent water resistance.
Patent Information
- Application Number
- CN202411433296.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing expansion fire-retardant coatings have shortcomings in terms of immersion resistance, shielding performance, carbon layer strength, coating thickness, thermal resistance at room temperature and low temperature, and are difficult to be used in narrow spaces. The good thermal conductivity of graphene will lead to a decrease in thermal resistance before expansion.
A single-component water-based system is adopted, combined with modified graphene oxide, hydrophobic aerogel materials, expandable graphite and aqueous petroleum resin to form a four-phase composite carbon source, and the thermal resistance performance of the coating is improved through the triple expansion insulation mechanism of aerogel, expandable graphite, and A-M-P expansion system.
It realizes multiple heat resistance functions of ultra-thin coatings, improves the strength and heat resistance of the carbon layer, enhances the water resistance and dielectric shielding performance of the coating, and has excellent heat resistance performance at normal temperatures and low temperatures, and plays an efficient heat resistance protection role in multiple key temperature ranges.
Smart Images

Figure CN118956212B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of fire retardant coatings, and in particular to a multi-heat-resistant ultra-thin intumescent fire retardant coating, a preparation method and application thereof. Background Art
[0002] Generally, the intumescent fire retardant coating is a ternary intumescent fire retardant system with ammonium polyphosphate-pentaerythritol-melamine as the main body. These three components have a synergistic effect under high temperature or flame, and none of them can be missing. When the coating encounters flames, the acid source (ammonium polyphosphate) first decomposes and releases inorganic acids. These inorganic acids cause the carbon source (pentaerythritol) material to lose water and carbonize, first forming inorganic acid salts, and then decompose with the increase of temperature to form a large amount of carbon, water, carbon dioxide and other substances, and the residues provide a carbon skeleton for the foaming layer. At the same time, the gas produced when the gas source (melamine) decomposes causes the softened coating to foam and expand, and the volume increases. The above reaction is an endothermic reaction, which can consume a lot of heat and is conducive to reducing the temperature of the coating system. Moreover, because the thermal resistance of the foaming layer itself is very large, it blocks the spread of heat to the substrate, delays the spread of the fire, and buys time for firefighting.
[0003] Defects and shortcomings: The existing intumescent fire retardant coatings themselves have poor immersion resistance and shielding properties; the carbon layer formed by the expansion of a single carbon source is not strong and is easy to collapse; the coating thickness is generally more than 2mm, which is difficult to use in narrow spaces; the coating has basically no expansion and thermal resistance capabilities at room temperature and low temperature (<260℃), resulting in insufficient protection in the initial stage of combustion.
[0004] In "CN113150671B non-ionic waterborne polyurethane-based expandable steel structure fire retardant coating and preparation method", aerogel is used as a component in the expandable steel structure fire retardant coating, but the action mechanism and benefits of aerogel in the system are not explained, nor is the role of aerogel before expansion in the ultra-thin fire retardant coating system analyzed and demonstrated.
[0005] Furthermore, the patent "CN113502077A A method for preparing a high-performance graphene fire-retardant coating" uses graphene oxide in the fire-retardant coating and explains its role, but the description of the action mechanism of graphene is not comprehensive enough, and the dispersibility and fire-retardant efficiency are not improved by modifying the graphene. In addition, due to the good thermal conductivity of graphene, when used in ultra-thin fire-retardant coatings, the heat resistance before expansion will drop sharply. The technology does not analyze this and provide targeted countermeasures.
[0006] In addition, the patent "CN108034315B Expanded Graphite Powder Water-Based Tunnel Fire Retardant Coating and Method of Use" uses expanded graphite to improve the fire resistance and immersion resistance of the fire retardant coating, but does not solve the problem of low thermal resistance before the coating expands. At the same time, the use of expanded graphite increases the looseness of the expanded carbon layer and reduces the strength of the carbon layer. This technology does not provide a corresponding solution.
[0007] Therefore, in order to solve the above problems, it is necessary to develop a multi-heat-resistant ultra-thin intumescent fire-retardant coating. Summary of the invention
[0008] In view of the existing technical problems, the present invention aims to provide an ultra-thin intumescent fire-retardant coating with multiple heat-resistant functions, which adopts a single-component water-based system and is very friendly to the environment and construction. At the same time, special film-forming materials and modified graphene oxide are used to overcome the problem of uneven dispersion of ordinary graphene in the coating. The modified graphene, hydrophobic aerogel material, expandable graphite and water-based petroleum resin together greatly improve the water resistance of the single-component water-based system. Graphene also constitutes a four-phase composite carbon source together with water-based petroleum resin, expandable graphite and traditional pentaerythritol. The composite carbon source provides a foamed and expanded carbon layer in a wider temperature range, making the carbon layer denser and more uniform. It also adopts a triple expansion insulation mechanism of aerogel, expandable graphite and AMP expansion system, which can play an efficient heat-resistant protection role in multiple key continuous temperature ranges such as 20-150°C and 150-300°C.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] A multi-heat-resistant ultra-thin intumescent fire-retardant coating, comprising the following components by weight:
[0011] Deionized water 10-25%, dispersant 0.5-2%, water-based bentonite 0.5-2%, water-based petroleum resin 2-5%, highly dispersed titanium dioxide 5-15%, micronized melamine 5-15%, pentaerythritol 5-15%, modified ammonium polyphosphate 15-30%, aerogel slurry 5-10%, expandable graphite 2-6%, alcohol ester dodecyl 1-3%, amine neutralizer 0.2-1%, graphene slurry 1-3%, water-based defoamer 0.2-0.5%, water-based copolymer emulsion 15-25%.
[0012] As an improvement, the dispersant is a high molecular weight block copolymer solution containing pigment-affinity groups with a solid content of 40±10%;
[0013] The water-based petroleum resin is a low-viscosity liquid aromatic petroleum resin that does not contain hydroxyl groups.
[0014] As an improvement, the highly dispersed titanium dioxide is an easily wettable rutile titanium dioxide with a narrow particle size distribution and surface treated with SiO2 and Al2O3, and the median particle size is 0.36 μm.
[0015] As an improvement, the micronized melamine is ultra-finely processed melamine powder with a median particle size of less than 5 μm and a particle size of less than 15 μm.
[0016] As an improvement, the modified ammonium polyphosphate is melamine formaldehyde resin coated crystalline type II ammonium polyphosphate;
[0017] The aerogel slurry is a uniform mixture of aerogel powder and water with a solid content of 10-14%.
[0018] As an improvement, the average particle size of the expandable graphite is 160 μm, the initial expansion temperature is 150° C., and the expansion volume is 200 ml / g;
[0019] The main component of the amine neutralizer is dimethylethanolamine;
[0020] The aqueous defoamer is a mixture of foam-breaking polysiloxane and hydrophobic particles in polyethylene glycol.
[0021] As an improvement, the graphene slurry is a modified graphene oxide dispersion with an average particle size of 5 μm, a thickness of less than 1.5 nm, and a solid content of 1%;
[0022] The modified graphene oxide dispersion preparation method is:
[0023] S1. Dispersing the purchased graphene oxide in DMF by ultrasonic means, and obtaining a graphene oxide dispersion with a mass fraction of 0.2% after ultrasonic dispersion for 1-3 hours;
[0024] S2. Add γ-glycidyloxypropyltrimethoxysilane dropwise to 0.2% graphene oxide dispersion under stirring at a speed of 800-1000 rpm, wherein the mass of γ-glycidyloxypropyltrimethoxysilane is 0.5% of the mass of graphene oxide dispersion. After the addition is completed, stir vigorously at a temperature of 100-140° C. for 0.5-2 h, then pour the liquid into a hydrothermal reactor and place it at a temperature of 160-220° C. for 6-12 h.
[0025] S3. After cooling the product obtained in step S2, the product was filtered and washed twice with DMF, and dried in a vacuum drying oven at 50° C. for more than 6 h. The dried modified graphene oxide powder was dispersed again in DMF by ultrasound at a mass ratio of 1:99 to form a modified graphene dispersion with a solid content of 1%.
[0026] As an improvement, the aqueous copolymer emulsion is a mixture of an aqueous dispersion obtained by polymerization of vinyl acetate-versatate vinyl ester and a vinyl acetate-ethylene aqueous copolymer emulsion, and the weight ratio of the two is 2:8 to 5:5.
[0027] In addition, the present invention also provides a method for preparing the above-mentioned multi-heat-resistant ultra-thin intumescent fire-retardant coating, and the preparation steps are as follows:
[0028] T1. Add 10-25% deionized water, 0.5-2% dispersant, and 0.5-2% aqueous bentonite in sequence under stirring at a speed of 200-400 rpm, and continue stirring for 5 minutes to form a mixture A;
[0029] T2. Under stirring at a speed of 500-800 rpm, 2-5% of water-based petroleum resin, 5-15% of highly dispersed titanium dioxide, 5-15% of micronized melamine, 5-15% of pentaerythritol, 15-30% of modified ammonium polyphosphate, 5-10% of aerogel slurry, 2-6% of expandable graphite, 1-3% of alcohol ester dodecyl sulfate, 0.2-1% of amine neutralizer, and 1-3% of graphene slurry are added to mixture A in sequence, and then stirred at a speed of 800-1000 rpm for 10 min to form mixture B;
[0030] T3. Add 0.2-0.5% of aqueous defoamer and 15-25% of aqueous copolymer emulsion to mixture B in sequence while stirring at a speed of 200-400 rpm. Continue stirring for 5 minutes. Filter the stirred materials through an 80-mesh filter and can them to obtain an ultra-thin intumescent fire retardant coating with multiple heat-resistant functions.
[0031] When applying the ultra-thin intumescent fire retardant coating with multiple heat-resistant functions, the coating is applied to the surface of the primer by spraying or brushing. When airless spraying is used, the thickness of each layer is 200-600 μm.
[0032] When air spraying and brushing are used, the thickness of each layer is 100-300μm;
[0033] The actual drying time of each coat at room temperature is 12 hours. After the previous coat is completely dry, it can be re-coated to achieve a higher film thickness.
[0034] The beneficial effects of the present invention are:
[0035] (1) The ultra-thin coating of the present invention has outstanding fireproof and heat-resistant properties. The heat-resistant capacity of the carbon layer of the ultra-thin coating is improved in three ways. First, the modified graphene nanomaterial is used innovatively. Through infrared spectrum analysis, it can be seen that the silane component is successfully grafted onto the graphene surface. Due to the steric hindrance of the functional groups on the surface after modification and the wrinkles of the graphene sheets, the interlayer spacing of the graphene increases and the dispersion is enhanced. With the help of XRD analysis, it is found that the interlayer spacing of the modified graphene nanomaterial is twice that before modification. With its excellent specific surface area and thermal conductivity, the coating is heated more evenly at the microscopic level, and the foaming expansion is more uniform and dense, which enhances Secondly, the strength and heat resistance of the expansion layer, especially the heat resistance of the ultra-thin coating, are enhanced by using a unique four-phase composite carbon source design, namely pentaerythritol, water-based petroleum resin, expandable graphite and graphene, which further enhances the strength and volume of the expanded carbon layer and forms a honeycomb microporous structure, thereby enhancing the fireproof and heat-resistant ability of the ultra-thin coating; thirdly, by using a mixed emulsion of vinyl acetate-versatate and vinyl acetate-ethylene (VAE) water-based copolymer, the mixed resin system reduces the constraint on the expansion of the coating, so that the coating has a high expansion ratio, and even the ultra-thin coating has a fully foamed and expanded heat-insulating carbon layer;
[0036] (2) The present invention has excellent heat resistance at room temperature and low temperature. First, aerogel is used to form a uniformly distributed microporous structure in the coating, which greatly reduces the thermal conductivity of the coating at room temperature and low temperature, so that the coating has a certain heat resistance capacity at room temperature and low temperature. Then, the characteristic of expandable graphite that it begins to expand rapidly at 150°C is used, so that the coating can exert an effective heat resistance effect before the traditional expansion system (starting at 290°C) is started. The three-level heat resistance mechanism enables the present invention to have a fireproof and heat-insulating effect in the full temperature range that other coatings cannot match;
[0037] (3) The present invention has excellent dielectric shielding and water resistance: the silane groups on the surface of the modified graphene are easy to react with organic resins, inorganic powders and substrates, thereby enhancing the crosslinking density and adhesion of the coating. In addition, the flake structure of the graphene material and the scaly structure of the expandable graphite are matched with each other, so that the coating forms an excellent "maze" effect, has excellent dielectric shielding performance, and has better water immersion resistance. At the same time, aerogel, as a highly hydrophobic nanomaterial, can significantly enhance the water resistance of the coating. In addition, the low viscosity and excellent water resistance of petroleum resin are used to form a coating on the resin and powder, which greatly improves the water immersion resistance of the coating and solves the common problem of poor water resistance of single-component water-based fire retardant coatings.
[0038] (4) The present invention has outstanding environmental and construction friendliness. The paint adopts a water-based system. The VOC of the entire product is extremely low (<30g / L), and the flash point is >93°C. It is very safe and environmentally friendly. At the same time, it is a single-component system and can be used immediately after opening. The unused paint can be reused after being sealed, avoiding waste caused by the paint preparation process and excessive mixing. It can be applied by spraying, roller brushing, smearing and other construction methods. The film thickness can reach 600-1000 microns at one time, which is a thick film type paint that is very easy to apply.
[0039] In summary, the ultra-thin intumescent fire retardant coating with multiple heat-barrier functions of the present invention has good water immersion resistance and fireproof and heat-insulating properties in a wide temperature range, and is particularly suitable for the field of fire retardant coating technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The schematic diagram of the preparation process of the ultra-thin intumescent fire retardant coating with multiple heat-blocking functions of the present invention;
[0041] Figure 2 It is a schematic diagram of the preparation process of the modified graphene oxide dispersion of the present invention. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0044] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0045] Example:
[0046] A multi-heat-resistant ultra-thin intumescent fire-retardant coating, comprising the following components by weight:
[0047] Deionized water 10-25%, dispersant 0.5-2%, water-based bentonite 0.5-2%, water-based petroleum resin 2-5%, highly dispersed titanium dioxide 5-15%, micronized melamine 5-15%, pentaerythritol 5-15%, modified ammonium polyphosphate 15-30%, aerogel slurry 5-10%, expandable graphite 2-6%, alcohol ester dodecyl 1-3%, amine neutralizer 0.2-1%, graphene slurry 1-3%, water-based defoamer 0.2-0.5%, water-based copolymer emulsion 15-25%.
[0048] First of all, the single-component water-based system is very friendly to the environment and construction. At the same time, the use of special film-forming materials and modified graphene oxide overcomes the problem of uneven dispersion of ordinary graphene in the coating. The modified graphene, hydrophobic aerogel material, expandable graphite and water-based petroleum resin together greatly improve the water resistance of the single-component water-based system.
[0049] Secondly, the modified graphene oxide material used in fire-retardant coatings for the first time also has excellent thermal conductivity, which makes the coating heat more evenly during a fire, and the carbon layer formed is more uniform and dense, avoiding the phenomenon of hollowing and large bubbles, and improving the fireproof and heat-insulating effect. At the same time, graphene also forms a four-phase composite carbon source together with water-based petroleum resin, expandable graphite, and traditional pentaerythritol. The composite carbon source provides a foaming and expanding carbon layer in a wider temperature range, making the carbon layer denser and more uniform.
[0050] In addition, the present invention also adopts a triple expansion insulation mechanism of aerogel, expandable graphite, and AMP expansion system, which can play an efficient heat-insulating protection role in multiple key continuous temperature ranges such as 20-150°C and 150-300°C.
[0051] Specifically, in the triple expansion insulation mechanism of the AMP expansion system, A stands for APP (ammonium polyphosphate), M stands for MEL (melamine), and P stands for PER (pentaerythritol). When heated, the coating melts, and then the pentaerythritol first decomposes at 277°C, followed by the catalyst ammonium polyphosphate decomposing at around 290°C to release ammonia and phosphoric acid, and the phosphoric acid further dehydrates by pyrolysis to release metaphosphoric acid and pyrophosphoric acid. These acids react with the carbonizing agent PER in the gas phase as dehydrating agents to dehydrate and carbonize PER. The foaming agent Mel decomposes at a slightly higher temperature (about 296°C) to release non-flammable gases such as ammonia, which, together with the water vapor in the reaction, causes the molten system to foam and expand, covering the surface of the combustible substrate, reducing the effect of external heat sources on the substrate, and thus protecting the substrate well.
[0052] Specifically, the coating can be used for fire retardant protection of power battery compartments and energy storage equipment. It can also be used in other occasions with high requirements on surface effects and ultra-thin fire protection needs, such as wooden buildings and plastic containers. The dry film thickness of 150 microns has very obvious heat-resistant protection effect.
[0053] Wherein, in order to promote the dispersion of the pigment, the dispersant is a high molecular weight block copolymer solution containing pigment affinity groups with a solid content of 40±10%;
[0054] In order to improve the adhesion and performance of the coating, the water-based petroleum resin is a low-viscosity liquid aromatic petroleum resin without hydroxyl groups.
[0055] In order to improve the hiding power of the coating, enhance the coloring ability and improve the leveling property of the coating, the highly dispersed titanium dioxide is an easily wettable rutile titanium dioxide with a narrow particle size distribution and surface treated with SiO2 and Al2O3, and the median particle size is 0.36 μm.
[0056] In order to enhance the flame retardant effect of the coating, strengthen the hardness and wear resistance, and improve the coating performance, the micronized melamine is a melamine powder that has been subjected to ultra-fine micronization treatment and has a median particle size of less than 5 μm and a particle size of less than 15 μm.
[0057] In order to enhance the flame retardant effect and heat absorption and cooling performance of the coating, form an expanded carbon layer, enhance the mechanical properties, and improve the water resistance and chemical resistance, the modified ammonium polyphosphate is a melamine formaldehyde resin-coated crystalline diammonium polyphosphate;
[0058] In order to improve the thermal insulation performance of the coating, reduce heat conduction, inhibit heat convection, enhance fire resistance, improve mechanical properties, and adjust optical properties, the aerogel slurry is a uniform mixture of aerogel powder with a solid content of 10-14% and water.
[0059] As one of the components of the four-phase composite carbon source, the expandable graphite has an average particle size of 160 μm, an initial expansion temperature of 150° C., and an expansion volume of 200 ml / g;
[0060] The main component of the amine neutralizer is dimethylethanolamine, and other types of amine neutralizers can also be used to adjust the pH value;
[0061] In order to eliminate foam and improve performance, the aqueous defoamer is a mixture of foam-breaking polysiloxane and hydrophobic particles in polyethylene glycol.
[0062] In addition, the graphene slurry is a modified graphene oxide dispersion with an average particle size of 5 μm, a thickness of less than 1.5 nm, and a solid content of 1%;
[0063] like Figure 2As shown, a method for preparing the modified graphene oxide dispersion is also provided, and the preparation steps are:
[0064] S1. Dispersing the purchased graphene oxide in DMF by ultrasonic means, and obtaining a graphene oxide dispersion with a mass fraction of 0.2% after ultrasonic dispersion for 1-3 hours;
[0065] S2. Add γ-glycidyloxypropyltrimethoxysilane dropwise to 0.2% graphene oxide dispersion under stirring at a speed of 800-1000 rpm, wherein the mass of γ-glycidyloxypropyltrimethoxysilane is 0.5% of the mass of graphene oxide dispersion. After the addition is completed, stir vigorously at a temperature of 100-140° C. for 0.5-2 h, and then pour the liquid into a hydrothermal reactor and place it at a temperature of 160-220° C. for 6-12 h.
[0066] S3. After cooling the product obtained in step S2, the product was filtered and washed twice with DMF, and dried in a vacuum drying oven at 50° C. for more than 6 h. The dried modified graphene oxide powder was dispersed again in DMF by ultrasound at a mass ratio of 1:99 to form a modified graphene dispersion with a solid content of 1%.
[0067] In order to enhance the film-forming and bonding properties of the coating, the aqueous copolymer emulsion is a mixture of an aqueous dispersion polymerized from vinyl acetate-versatate and a vinyl acetate-ethylene aqueous copolymer emulsion, with a weight ratio of 2:8 to 5:5.
[0068] like Figure 1 As shown, in addition, the present invention also provides a method for preparing the above-mentioned multi-heat-resistant ultra-thin intumescent fire-retardant coating, and the preparation steps are as follows:
[0069] T1. Add 10-25% deionized water, 0.5-2% dispersant, and 0.5-2% aqueous bentonite in sequence while stirring at a speed of 200-400 rpm, and continue stirring for 5 minutes;
[0070] T2. Under stirring at a speed of 500-800 rpm, add 2-5% water-based petroleum resin, 5-15% highly dispersed titanium dioxide, 5-15% micronized melamine, 5-15% pentaerythritol, 15-30% modified ammonium polyphosphate, 5-10% aerogel slurry, 2-6% expandable graphite, 1-3% alcohol ester dodecyl sulfate, 0.2-1% amine neutralizer, and 1-3% graphene slurry in sequence, and stir at a speed of 800-1000 rpm for 10 minutes;
[0071] T3. While stirring at a speed of 200-400rpm, add 0.2-0.5% of aqueous defoamer and 15-25% of aqueous copolymer emulsion in sequence, and continue stirring for 5 minutes. Filter the stirred materials through an 80-mesh filter and can them to obtain an ultra-thin intumescent fire retardant coating with multiple heat-resistant functions.
[0072] When applying the ultra-thin intumescent fire retardant coating with multiple heat-resistant functions, the coating is applied to the surface of the primer by spraying or brushing. When airless spraying is used, the thickness of each layer is 200-600 μm.
[0073] When air spraying and brushing are used, the thickness of each layer is 100-300μm;
[0074] The actual drying time of each coat at room temperature is 12 hours. After the previous coat is completely dry, it can be re-coated to achieve a higher film thickness.
[0075] Embodiment 1-4:
[0076] The specific component contents of the ultra-thin intumescent fire retardant coatings with multiple heat-blocking functions of Examples 1-4 are shown in Table 1 below:
[0077] Table 1
[0078]
[0079] Comparative Examples 1-3:
[0080] The specific component contents of the coatings of Comparative Examples 1-3 are shown in Table 2 below:
[0081] Table 2
[0082]
[0083] The coatings in Examples 1-4 and Comparative Examples 1-3 were prepared by the preparation method described in the examples. A coating with a thickness of 500 μm was prepared from the coatings obtained in Examples 1-4 and Comparative Examples 1-3. The drying time was tested according to GB / T 1728. After 7 days of self-drying, the coating strength, expansion ratio, carbon layer strength, fire resistance time, water resistance, and moisture and heat resistance of the coating were tested. The test method is as follows:
[0084] The coating strength is tested in accordance with 6.4.4 of GB 14907-2018. The expansion ratio, carbon layer strength and fire resistance time are evaluated after testing with a small experimental furnace and referring to Appendix A of GB 14907-2018. The ratio of the thickness of the highest point of the carbon layer to the thickness of the original coating is the expansion ratio. Use a blade to cut the carbon layer in the direction perpendicular to the surface of the substrate to judge the strength of the carbon layer: if the incision is complete and does not collapse when pressed lightly, it is dense; if the incision is complete and collapses when pressed lightly, it is relatively dense; if the incision collapses slightly, it is general; if the incision causes the carbon layer to collapse, it is loose. The fire resistance time is the time it takes for a 1mm coating to reach the ultimate fire resistance temperature. The longer the fire resistance time, the better the fire resistance of the coating.
[0085] The water resistance is tested in accordance with 6.4.4 of GB 14907-2018. After the test, the coating should not have delamination, shedding, hollowing or cracking. The fire resistance time tested after the paint film is intact within the specified time should not exceed 35%.
[0086] The moisture and heat resistance is tested in accordance with 6.4.12 of GB 14907-2018. After the test, the coating should not have delamination, shedding, hollowing or cracking. After the paint film is intact within the specified time, the fire resistance time decay should not exceed 35%.
[0087] The specific test results are shown in Table 3 below:
[0088] Table 3
[0089]
[0090] The fire-resistant time refers to the time required for the back surface temperature to reach 500°C when the front side is burned by a 1050°C blowtorch flame.
[0091] Comparative Example 1 is a conventional intumescent fire retardant coating solution. It can be seen that the conventional fire retardant coating without adding structural design and hydrophobic materials has poor water resistance, and because the three-level heat resistance and composite carbon source design are not adopted, the fire resistance time of the thin coating is low. Comparative Example 2 has improved water resistance of the coating due to the addition of petroleum resin and graphene. Due to the addition of composite carbon source, the strength, density and fire resistance time of the carbon layer are improved. Comparative Example 3 adds expandable graphite and aerogel, and the water resistance is further improved. At the same time, the three-level heat resistance mechanism greatly improves the fire resistance time of the coating. However, due to the low resin content, the water resistance and moisture resistance are not ideal, and the coating and expanded carbon layer have low strength. More petroleum resin is used in Example 1, which causes the coating to dry slowly and the coating strength is low. Too much aerogel is added in Example 2, and the aerogel has a large oil absorption, which squeezes out the addition ratio of other flame retardant powders, resulting in a lower expansion ratio and a shorter fire resistance time. Too much expandable graphite was added in Example 3, which resulted in a loose expanded carbon layer and also affected the fire resistance time of the coating. Example 4 uses a three-level thermal insulation design and a multiple composite carbon source design to make the carbon layer have an excellent expansion ratio, high uniformity and density, and a fire resistance time that is 49% higher than that of the ordinary comparative example 1. At the same time, due to the shielding structure and hydrophobic material, the coating has excellent shielding and water resistance. In summary, the various performance indicators of Example 4 reflect the uniqueness and advancement of the present invention, and the coating can be widely used in occasions including but not limited to: power battery compartments, energy storage equipment, steel structure fire protection, and fire retardancy of various flammable materials.
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A multi-heat-resistant ultra-thin intumescent fire-retardant coating, characterized in that: The components include the following by weight: Deionized water 10-25%, dispersant 0.5-2%, water-based bentonite 0.5-2%, water-based petroleum resin 2-5%, highly dispersed titanium dioxide 5-15%, micronized melamine 5-15%, pentaerythritol 5-15%, modified ammonium polyphosphate 15-30%, aerogel slurry 5-10%, expandable graphite 2-6%, alcohol ester dodecyl 1-3%, amine neutralizer 0.2-1%, graphene slurry 1-3%, water-based defoamer 0.2-0.5%, water-based copolymer emulsion 15-25%; The modified ammonium polyphosphate is melamine formaldehyde resin coated crystalline type II ammonium polyphosphate; The graphene slurry is a modified graphene oxide dispersion with an average particle size of 5 μm and a thickness of less than 1.5 nm, and a solid content of 1%; The modified graphene oxide dispersion preparation method is: S1. Dispersing the purchased graphene oxide in DMF by ultrasonic means, and obtaining a graphene oxide dispersion with a mass fraction of 0.2% after ultrasonic dispersion for 1-3 hours; S2. Under stirring at a speed of 800-1000 rpm, add γ-glycidyloxypropyltrimethoxysilane in an amount of 0.5% of the dispersion, and after the addition is completed, stir vigorously at a temperature of 100-140°C for 0.5-2h, then pour the liquid into a hydrothermal reactor and place it at a temperature of 160-220°C for 6-12h; S3. After cooling the product obtained in step S2, the product was filtered and washed twice with DMF, and dried in a vacuum drying oven at 50° C. for more than 6 h. The dried modified graphene oxide powder was dispersed again in DMF by ultrasound at a mass ratio of 1:99 to form a modified graphene dispersion with a solid content of 1%.
2. A multi-heat-resistant ultra-thin intumescent fire-retardant coating according to claim 1, characterized in that: The dispersant is a high molecular weight block copolymer solution containing pigment affinity groups with a solid content of 40±10%; The water-based petroleum resin is a low-viscosity liquid aromatic petroleum resin that does not contain hydroxyl groups.
3. A multi-heat-resistant ultra-thin intumescent fire-retardant coating according to claim 1, characterized in that: The highly dispersed titanium dioxide is an easily wettable rutile titanium dioxide with a narrow particle size distribution and surface treated with SiO2 and Al2O3, and the median particle size is 0.36 μm.
4. A multi-heat-resistant ultra-thin intumescent fire-retardant coating according to claim 1, characterized in that: The micronized melamine is ultra-micronized melamine powder with a median particle size of less than 5 μm and a particle size of less than 15 μm.
5. The multi-heat-resistant ultra-thin intumescent fire-retardant coating according to claim 1, characterized in that: The aerogel slurry is a uniform mixture of aerogel powder and water with a solid content of 10-14%.
6. The multi-heat-resistant ultra-thin intumescent fire-retardant coating according to claim 1, characterized in that: The expandable graphite has an average particle size of 160 μm, an initial expansion temperature of 150° C., and an expansion volume of 200 ml / g; The main component of the amine neutralizer is dimethylethanolamine; The aqueous defoamer is a mixture of foam-breaking polysiloxane and hydrophobic particles in polyethylene glycol.
7. The multi-heat-resistant ultra-thin intumescent fire-retardant coating according to claim 1, characterized in that: The aqueous copolymer emulsion is a mixture of an aqueous dispersion formed by polymerization of vinyl acetate-versatate vinyl ester and a vinyl acetate-ethylene aqueous copolymer emulsion, and the weight ratio of the two is 2:8 to 5:
5.
8. A method for preparing the multi-heat-resistant ultra-thin intumescent fire-retardant coating according to any one of claims 1 to 7, characterized in that: The preparation steps are as follows: T1. Add 10-25% deionized water, 0.5-2% dispersant, and 0.5-2% aqueous bentonite in sequence while stirring at a speed of 200-400 rpm, and continue stirring for 5 minutes; T2. Under stirring at a speed of 500-800 rpm, add 2-5% water-based petroleum resin, 5-15% highly dispersed titanium dioxide, 5-15% micronized melamine, 5-15% pentaerythritol, 15-30% modified ammonium polyphosphate, 5-10% aerogel slurry, 2-6% expandable graphite, 1-3% alcohol ester dodecyl sulfate, 0.2-1% amine neutralizer, and 1-3% graphene slurry in sequence, and stir at a speed of 800-1000 rpm for 10 minutes; T3. While stirring at a speed of 200-400rpm, add 0.2-0.5% of aqueous defoamer and 15-25% of aqueous copolymer emulsion in sequence, and continue stirring for 5 minutes. Filter the stirred materials through an 80-mesh filter and can them to obtain an ultra-thin intumescent fire retardant coating with multiple heat-resistant functions.
9. An application of the multi-heat-resistant ultra-thin intumescent fire-retardant coating according to any one of claims 1 to 7, characterized in that: Apply the paint on the primer surface by spraying or brushing. When airless spraying is used, the thickness of each layer is 200-600μm. When air spraying and brushing are used, the thickness of each layer is 100-300μm; The actual drying time of each coat at room temperature is 12 hours. After the previous coat is completely dry, it can be re-coated to achieve a higher film thickness.
Citation Information
Patent Citations
Expanded graphite powder water-based tunnel fireproof coating and its application method
CN108034315B
Nonionic waterborne polyurethane-based intumescent fire-retardant coating for steel structures and its preparation method
CN113150671B
Preparation method of graphene high-performance fireproof coating
CN113502077A
Waterborne ultrathin-type steel-structure fireproof coating
CN107400423A
Modified graphene oxide water-based intumescent fireproof coating and preparation method thereof
CN117801587A